The relationship between organizational commitment and job sastisfaction among non-academic employees at Universiti Teknologi Mara Sarawak, Samarahan Campus 2/ Anatasia Menti Albert - Albert, Anatasia Menti (2016)
This study is to study the relationship between Organizational Commitment (Affective, Continuance and Normative) and Job Satisfaction among the non-academic employees at Universiti Teknologi MARA Sarawak, Samarahan Campus 2. Therefore, the study will contribute to the extent of management and organizational behavior. In the beginning of this study, the purpose, research questions, significant of this study and other relevant for this study is indicated. In order to collect the data, the researcher used questionnaires as an instrument to find out the information from the respondents. The research was using the Statistical Packages for the Social Sciences (SPSS), version 20.0 in the data analysis process. The result showed that all the components of Organizational Commitment are having positive relationship with the Job Satisfaction of the employees at Universiti Teknologi MARA Sarawak, Samarahan Campus 2.